Determination and correlation of solid-liquid phase equilibrium and phase diagram for multicomponent system of mixed dibasic acids. (III) Ternary system of succinic acid + glutaric acid + ethanol system. (April 2017) - Li, Rongrong; Lin, Li; Feng, Wenjuan; Xu, Jiayu; Du, Cunbin; Zhao, Hongkun
Graphical abstract: Highlights: SLE for ternary system of succinic acid + glutaric acid + ethanol was determined. The ternary phase diagrams were constructed at 283.15 K, 303.15 K and 313.15 K. The phase diagrams were correlated and calculated by NRTL and Wilson models. The densities of the equilibrium liquid phase were obtained and correlated. Abstract: The solid-liquid phase equilibrium for ternary system of succinic acid + glutaric acid + ethanol was determined by an isothermal saturation method at the three temperatures of (283.15, 303.15 and 313.15) K under atmosphere pressure. Three isothermal phase diagrams were built based on the measured mutual solubility data. There were two pure solids formed in the ternary system at a certain temperature, which corresponded to pure succinic acid and pure glutaric acid and were confirmed by Schreinemaker's method of wet residue and X-ray powder diffraction. The ternary phase diagram included one co-saturated point, two boundary curves, and three crystalline regions. The crystallization region of glutaric acid was smaller than that of succinic acid at each temperature. In addition, two thermodynamic models, NRTL and Wilson were employed to correlate and calculate the mutual solubility data for the ternary succinic acid + glutaric acid + ethanol system. The largest RMSD value for the ternary system of succinic acid + glutaric acid + ethanol was 0.43, and the maximum value of RAD was 3.0%. The Wilson model and NRTL model may all be employed to describe the mutual solubility behavior for the ternary system of succinic acid + glutaric acid + ethanol at various temperatures. Furthermore, the densities of the equilibrium liquid phase were obtained and correlated with an empirical equation.